SP10.1.10 Management of Acute Sigmoid Volvulus in a Single Scottish Health Board. (9th August 2022) - May, Victoria; Drever, Sara Katherine; Ramsay, George
Abstract: Aim: The Emergency General Surgery guidelines from the ACPGBI were recently published and recommend that definitive management should be planned on index admission with sigmoid volvulus. However, the evidence base for these recommendations was low. We aim assess the current practice of Sigmoid Volvulus (SV) in a Single Scottish Health board. Method: A retrospective review of patients with acute SV managed at two hospitals between 2011 and 2021 was conducted. Individuals were identified through inpatient coding and case notes reviewed electronically. Operative intervention, colonoscopic decompression and short and long term outcomes were noted. Results: Of 105 patients treated, 41 were female. The mean age at presentation was 73.2 (range: 38–94 years). In total, 70 patients (66.7%) underwent decompression alone and 35 (33.3%) were treated with surgical intervention. There was no difference in mean age, number of co-morbidities and number of previous operations between the two groups. Of the decompression group, 35 (50%) presented on a single occasion. However, the mean number of re-presentations was 3.3 (range 2–29) and the mean time to re-presentation was 136.5 days (range 5–1224 days). There were no recorded inpatient deaths following surgical intervention. Conclusion: The most common method of acute SV management has been decompression on its own. There were no differences observed in patient demographics between the intervention groups, suggesting that there are no set criteria to determine method of intervention. However, representation remains commonplace and operative intervention had few complications indicating a likely required increase in definitive surgical approaches.